ENHANCING TEENAGERS’ KNOWLEDGE ABOUT MENARCHE CARE IN ELEMENTARY SCHOOL AGE THROUGH AUDIOVISUAL MEDIA - Sopiah, Popi; Siti Sukaesih, Nunung; Nuryani, Reni; Haryeti, Popon; Wulan Lindasari, Sri (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Teenagers are defined as the transition period from childhood to adulthood. In Indonesia, according to population projection data (2014), the number of teenagers reaches around 65 million or 25 percent over the 255 million population (Ministry of Health, 2015). In the 2014-2019 health development target, teenager reproductive problems are one of the biggest issues that must be a concern, one of which is the understanding of menarche or menstruation experienced. Data shows that a quarter of teens never talks about menstruation before experiencing menarche. Insufficient knowledge about menarche causes anxiety problems in adolescents, unpreparedness in dealing with menarche, and poor personal hygiene during menstruation which can have an impact on reproductive health. Based on this analysis, it is considered important to carry out community service to improve understanding and knowledge of menarche care at elementary school age. Audiovisual teaching media was used as a material and method. The sample size for community services was 50 participants, from 4 to 6-grade students. A self-administered questionnaire was used for pre and post-test data collection. The results showed differences between pre and post-test about knowledge of menarche care. Before applying the community service, there were 18% of girls were aware of menarche and menstrual hygiene. Meanwhile, the post-test result showed an improvement to 64%. Significant differences were observed among girls in terms of knowledge and perception related to menarche care. The promotion of health through education is expected to be able to increase the knowledge of young girls, so they can achieve both physical and psychological care and health.